Mengenalkan Filsafat Teologi (Konsep Tentang Allah) pada Anak Usia Dini Melalui Metode Bernyanyi Islami di RA Masithoh Bantar - Suratiyah, Suratiyah (Indo-MathEdu Intellectuals Journal, 2024)
This research was motivated by the importance of introducing theological philosophy (the concept of God) to children from an early age. Recognition of the concept of God is very important to be developed in early childhood so that children do not grow and develop in a void of faith, moreover the recognition of the concept of God is as important as cognitive, social and other development. One of the efforts to introduce theological philosophy to early childhood in RA Masithoh Bantar is by learning through Islamic singing. The purpose of this article is to find out how the Islamic song method is applied in introducing theological philosophy in early childhood. The type of research used is qualitative research. Data collection techniques through observation, interviews, and documentation, so it is known that knowledge of the attributes of Allah Almighty in beings can be enhanced by the application of Islamic songs. Data analysis is carried out with stages of data reduction, data presentation, and conclusions. The results of this study found that with the implementation of learning using the Islamic singing method can increase knowledge about the attributes of God, God's creatures, how to love God's creatures and can introduce theological philosophy in early childhood in RA Masithoh Bantar